DIELECTRIC STUDIES IN Li2O AND CoO DOPED BOROPHOSPHATE GLASSES - Talari, Sankarappa; Ashwajeet, J. S.; Ramanna, R.; Praveenkumar, K. (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Borophosphate glasses in the compositions, (B2O3)0.2 . (P2O5)0.3 . (Li2O) 0.5-X . (CoO) X, wherex = 0.05, 0.1, 0.15, 0.25, 0.30, 0.35, 0.40 and 0.45 were prepared at 1400K by following melt quenching method. Their amorphous nature was confirmed by XRD studies and was investigated for dielectric properties in the frequency range from 100Hz to 1MHz and temperature range from 300K to 573K. The conductivity was derived from the dielectric spectrum. The frequency exponent, s, dc and ac components of the conductivity were determined. The temperature dependence of conductivity at different frequencies was analyzed using Motts small polaron hopping model, and the high temperature activation energy has been estimated and discussed. The variation of conductivity and activation energy with composition revealed a changeover of conduction mechanism from predominantly ionic to electronic regime for mole fractions of CoO between 0.3 and 0.35. This is a new result. Hunts model has been employed to analyze frequency dependence of conductivity. Relaxation features of the dielectric properties have been extracted from the analysis of electric moduli with frequency. Activation energy for relaxation mechanism has been determined. Frequency exponent was found to be temperature dependent. Quantum mechanical theory and correlated barrier hopping models were found to be inadequate to explain frequency exponent behavior with temperature. For the first time that borophosphate glasses doped with Li2O and CoO were studied for dielectric properties and ac conductivity as a function of temperature and frequency and the data has been analysed thoroughly.